Dc motor drive and data acquisition system/ Ismailiah Mohd Rezuki - Mohd Rezuki, Ismailiah (1995)
This paper discusses the development of a simple dc motor drive system for laboratory experiments. The system is capable of driving the dc motor coupled to a load over a wide range of speed, from zero to base speed. This is achieved by feeding the armature with variable voltage supply generated by the single phase thyristor fully-controlled rectifier. All the experimental parameters, voltage, current and speed, are measured by the respective transducers and converted into its digital equivalent by the analog-to-digital converted. The digital signals are then transmitted in sequentially into the computer via interface unit . The operation of the system is controlled by the computer software.